Case Report: A Novel Variant c.2262+3A>T of the SCN5A Gene Results in Intron Retention Associated With Incessant Ventricular Tachycardias - Yin, Jie; Zhou, Jia; Chen, Jinlong; Xu, Ting; Zhang, Zhongman; Zhang, Han; Yuan, Chang; Cheng, Xueying; Qin, Yuming; Zheng, Bixia; Wang, Chunli; Yang, Shiwei; et al. (Frontiers in Medicine, 2021)
Objective Voltage-gated sodium channel Nav1.5 encoded by the SCN5A gene plays crucial roles in cardiac electrophysiology. Previous genetic studies have shown that mutations in SCN5A are associated with multiple inherited cardiac arrhythmias. Here, we investigated the molecular defect in a Chinese boy with clinical manifestations of arrhythmias. Methods Gene variations were screened using whole-exome sequencing and validated by direct Sanger sequencing. A mini-gene assay and reverse transcription PCR (RT-PCR) were performed to confirm the effects of splice variants in vitro. Western blot analysis was carried out to determine whether the c.2262+3A>T variant produced a truncated protein. Results By genetic analysis, we identified a novel splice variant c.2262+3A>T in SCN5A gene in a Chinese boy with incessant ventricular tachycardias (VT). This variant was predicted to activate a new cryptic splice donor site, was identified by in silico analysis. The variant retained 79 bp at the 5′ end of intron 14 in the mature mRNA. Furthermore, the mutant transcript created a premature stop codon at 818 amino acids (p.(R818*)), which produced a truncated protein. Conclusion We verified the pathogenic effect of splicing variant c.2262+3A>T which disturbed the normal mRNA splicing and caused a truncated protein, suggesting that splice variants play an important role in the molecular basis of early onset incessant ventricular tachycardias, and careful molecular profiling of these patients will be essential for future effective personalized treatment options.